HOSPITAL MANAGEMENT ON PATIENT SAFETY AND PATIENT SAFETY CULTURE DURING COVID-19 PANDEMIC: A SCOPING REVIEW - Navisya Dewi Putri Meidina; Mardiati Nadjib (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
The world is facing significant changes in care delivery, including growing complexity, resource problems, and manpower shortages. The COVID-19 pandemic exposed any organizational weaknesses, including patient safety risks. Patient safety is the avoidance and reduction of potential hazards, errors, and harm, sometimes known as adverse consequences, that may occur during the provision of healthcare or in healthcare settings. The databases Proquest, PubMed, and Scopus were used to conduct a scoping review. The scoping review was conducted employing the Arksey and O'Malley methodological framework and led by the (PRISMA-ScR) checklist and explanation. The electronic search retrieved 468 articles. Screening based on abstracts, titles and full-text only identified 6 articles focused discuss about Patient Safety. In clinical settings, nurses are likely to be the first to identify patient safety hazards. Hospital administration is a crucial element of a pleasant work environment that encourages the growth of patient safety. Management and clinical leaders should cooperate with personnel to develop a shared vision of the organization's safety culture that can be represented in its policies and procedures. In order to create matured work environment through empowerment individual workers, organization should start with the top level of hospital administration and develop well-structured communication of each individual healthcare workers.